Genome Characteristics Reveal the Biocontrol Potential of Actinobacteria Isolated From Sugarcane Rhizosphere - Wang, Zhen; Solanki, Manoj Kumar; Yu, Zhuo-Xin; Anas, Muhammad; Dong, Deng-Feng; Xing, Yong-Xiu; Malviya, Mukesh Kumar; Pang, Fei; Li, Yang-Rui (Frontiers in Microbiology, 2021)
To understand the beneficial interaction of sugarcane rhizosphere actinobacteria in promoting plant growth and managing plant diseases, this study investigated the potential role of sugarcane rhizospheric actinobacteria in promoting plant growth and antagonizing plant pathogens. We isolated 58 actinobacteria from the sugarcane rhizosphere, conducted plant growth promoting (PGP) characteristics research, and tested the pathogenic fungi in vitro. Results showed that BTU6 (Streptomyces griseorubiginosus), the most representative strain, regulates plant defense enzyme activity and significantly enhances sugarcane smut resistance by regulating stress resistance-related enzyme (substances (POD, PAL, PPO, TP) in sugarcane) activity in sugarcane. Genomic evaluation indicated that BTU6 has the ability to biosynthesize chitinase, β-1,3-glucanase and various secondary metabolites, and plays an important role on the growth of sugarcane plants under biotic stress. Potential mechanisms of the strain in improving the disease resistance of sugarcane plants, and its potential in biodegrading exogenous chemicals were also revealed. This study showed the importance of sugarcane rhizosphere actinobacteria in microbial ecology and plant growth promotion.